2020
DOI: 10.21273/jashs04887-19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Chinese Corylus heterophylla and Corylus kweichowensis Using Simple Sequence Repeat Markers

Abstract: Corylus heterophylla and Corylus kweichowensis are economically and ecologically important nut-producing woody shrubs that are distributed across northern and southern regions of China. However, few studies have examined the genetic diversity and genetic relationships between C. heterophylla and C. kweichowensis, and their taxonomic relationships have been questioned. In this study, 796 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The taxonomic status of the three ecotypes ( C. heterophylla , C. kweichowensis , and C. yunnanensis ) within C. heterophylla complex has long been unsolved, with several controversial treatments proposed: (i) both C. kweichowensis and C. yunnanensis were the botanical varieties of C. heterophylla [ 10 ]; (ii) C. yunnanensis was treated as a distinct species, while C. kweichowensis was the variety of C. heterophylla [ 39 ]; and (iii) the three were all distinct species [ 21 , 40 ]. However, these conclusions were reached based on limited diagnostic morphologies and traditional molecular markers that were insufficient to clarify the evolutionary relationships among sibling species.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic status of the three ecotypes ( C. heterophylla , C. kweichowensis , and C. yunnanensis ) within C. heterophylla complex has long been unsolved, with several controversial treatments proposed: (i) both C. kweichowensis and C. yunnanensis were the botanical varieties of C. heterophylla [ 10 ]; (ii) C. yunnanensis was treated as a distinct species, while C. kweichowensis was the variety of C. heterophylla [ 39 ]; and (iii) the three were all distinct species [ 21 , 40 ]. However, these conclusions were reached based on limited diagnostic morphologies and traditional molecular markers that were insufficient to clarify the evolutionary relationships among sibling species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that SSR loci developed from European hazelnuts were highly conserved and universal in other Corylus species, e.g., C. heterophylla and C. kweichowensis [15], C. colurna [44], and C. mandshurica [14]. However, a very limited number of SSRs have been tested in Ping'ou hybrid hazelnut so far.…”
Section: Discussionmentioning
confidence: 99%
“…SSR markers have the distinguishing features of multi-allelic, co-dominant inheritance patterns, reproducibility, high polymorphism, locus specificity, and transferability to related species and genera [5]. At present, more than 700 SSR loci have been developed in Corylus [6][7][8][9][10][11][12][13], and have been widely used in population structure assessment [14][15][16], germplasm identification and genetic diversity analysis [17][18][19][20], linkage map construction [21][22][23][24], and molecular marker-assisted selection [25,26]. In our previous study, we identified some cultivars of Ping'ou hybrid hazelnut by using the EST-SSR markers we developed in a pistil transcriptome [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hazelnut, produced by a shrub or small tree of Corylus Linn. in the family Betulaceae, is one of the four major dried fruits in the world and was reported to have originated in southwest China in the middle Eocene (~43.6 million years ago) [1,2]. Among Chinese hazel plants, Corylus heterophylla, mainly distributed in northern China, has been developed and utilized, while Corylus kweichowensis, predominantly distributed in southern China, has important potential utilization value [3].…”
Section: Introductionmentioning
confidence: 99%